Specular reflection of uniform plane waves by a lossy chiral Dallenbach layer - Smith, Anthonie Gronum (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Electronics)) -- University of Stellenbosch, 1990.